ENSURING THE SUSTAINABILITY OF MONETARY CIRCULATION IN UKRAINE IN THE CONTEXT OF REALIZATION OF MONETARY POLICY INSTRUMENTS - Пшик , Богдан (Socio-economic relations in the digital society, 2019)
A special feature of the modern economy is to ensure the stability of monetary circulation, which is a prerequisite for ensuring economic equilibrium for any country. This is manifested in the stability of all prices and tariffs, the full satisfaction of solvent demand for goods and services, the balance of consumption and savings, the correspondence of the rates of turnover of money and the mass of goods, and, ultimately, the balanced development of the economy due to the observance of the law of monetary circulation. It is proved that monetary policy contributes to the achievement of the projected socio-economic goals of society and is an essential factor in ensuring the stability of monetary circulation, creating the appropriate basis – price stability and low inflation in the long run. It is when implementing its strategy of monetary policy that the NBU is guided by the gradual transition to a monetary regime based on price stability. This transition, as evidenced by the experience of countries with the regime of inflation targeting, is able to provide low and projected inflation, which will lead to a significant increase in real incomes of the population and business entities, changes in the structure of the consumer basket of the population, improvement of living standards in the country, growth of volumes of the domestic market, which will be the main driving force of socio-economic growth in Ukraine. The main directions of ensuring the stability of monetary circulation on the basis of monetary policy instruments are: undeniable priority to achieve and maintain price stability in comparison with other monetary policy objectives and objectives; promising decision making based on a macroeconomic basis; Transparency of the activities of the central bank regarding decisions in the sphere of money circulation and monetary policy; ensuring a high level of independence of the central bank; observance of the floating exchange rate regime.